Online food ordering application using Boyer-Moore algorithm / Muhammad Zulhilmie Dzulkifli - Dzulkifli, Muhammad Zulhilmie (2021)
In modern society, with the advent of technology, people can easily share information, interact with each other and do their job on an online platform. Based on the previous report, some issues arise, such as time-consumption between the staff and the customer when ordering, lack of details and inconsistency of the manual system data. The manual method often has a lack of knowledge that the menu that shows the customer does not provide any information that customers need, such as an image of the food or ingredients used in the menu. To solve this problem, a mobile application has been proposed for customers to order their food and drink easily and the owner can manage the order without any restrictions. The main goal of this study is to create an online food ordering app using the corresponding Boyer-Moore string matching algorithm. The application evaluation process is carried out by the developer's functionality test to ensure that there are no unnecessary issues in this app, especially in the main feature. With high precision, the Boyer-Moore algorithm will search faster. The future work of this project is to create further features that will make this app very successful.